The use of methotrexate in rheumatoid arthritis. Recommendations of the All-Russian public organization “Association of Rheumatologists of Russia” - E. L. Nasonov; V. N. Amirjanova; Y. A. Olyunin; Y. V. Muravyev; A. A. Baranov; E. V. Zonova; E. N. Otteva; A. I. Zagrebneva; D. I. Abdulganieva; P. I. Pchelnikova (Научно-практическая ревматология)
Rheumatoid arthritis (RA) is the most frequent immunoinflammatory (autoimmune) rheumatic disease characterized by chronic erosive arthritis and systemic damage to internal organs. The data obtained in the course of basic research on deciphering the mechanisms of action of methotrexate (MT) and the materials of numerous randomized placebocontrolled trials, observational studies and national registries have strengthened the position of MT as the “gold standard” of RA pharmacotherapy and a key component of the “Treatment to Target” strategy. This was the basis for the development of new recommendations of the Association of Rheumatologists of Russia (ARR) concerning the use of MT in RA, according to which MT is considered as the drug of “choice” for induction and maintenance of remission in patients with early and advanced RA, including those who need combination therapy of MT with glucocorticoids, standard Disease-Modifying Antirheumatic Drugs (DMARDs), biologics and targeted synthetic DMARDs. Special attention is paid to the safety of MT therapy and the impact of MT on comorbid pathology associated with cardiovascular complications and interstitial lung disease. Implementation of the ARR recommendations into clinical practice will reduce the risk of disability and improve life prognosis in patients with RA.